Non-renewable energy, green technological innovation, and CO2 emissions in South Asia - Fatima Farooq; Chan Wei Leong; Muhammad Faheem; Daouia Chebab; Asma Nousheen (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2024)
Transitioning from fossil fuel usage to the adoption of green energy is crucial for mitigating the adverse impacts of greenhouse gas emissions. There is an urgent imperative to shift the economy away from reliance on non-renewable energy sources towards renewable alternatives to address environmental pollution effectively. This research aims to analyze the impact of non-renewable energy, green technological innovations, GDP, population, and industry on CO2 emissions across five South Asian countries, namely Pakistan, Bangladesh, India, Nepal, and Sri Lanka. Employing the Autoregressive Distributed Lag (ARDL) model and NARDL, the present study examined data spanning from 1985 to 2021. This study used STATA software to determine the association between variables. The findings indicate that an increase in non-renewable energy consumption leads to higher CO2 emissions across all five studied countries, while a decrease in non-renewable energy consumption helps reduce CO2 emissions. Population growth and GDP contribute to increase carbon emissions, whereas green technological innovations lead to a reduction in CO2 emissions in India, Sri Lanka and Nepal but boost CO2 levels in Pakistan and Bangladesh. Industrialization also showed different impact in different countries as it mitigated CO2 emissions in Pakistan, Bangladesh and Nepal but degrades the environment in India and Sri Lanka.
Keywords: 330; Non-renewable energy; green technological innovation; CO2 emissions; industrialization; South Asia